Evaluasi Program Pembelajaran Pendidikan Agama Islam Menggunakan Model Context, Input, Process and Product di SDN 430 Pandoso Kabupaten Luwu - Harun, Despita; Nursyamsi, Nursyamsi; Hasriadi, Hasriadi (ARZUSIN, 2025)
This article discusses the evaluation of the Islamic Religious Education learning program at SDN 430 Pandoso, Luwu Regency using the Context, Input, Process and Product (CIPP) evaluation model. The purpose of this study is for researchers to determine and assess the success of the learning program and its suitability for the Islamic learning curriculum at the school. This research discusses program evaluation based on the CIPP model proposed by Stufflebeam. In this study, context, input, process, and product are used as the four elements of evaluation. The study involved 32 fourth and fifth grade students and Islamic religious education teachers. Information for this study was collected through documentation, interviews, observation and questionnaires. Furthermore, qualitative data analysis and quantitative data analysis were used as methods to analyze the data in this study. The results of this study indicate that there are discrepancies between programs and learning plans, human resources, facilities and infrastructure, learning media, learning methods and student learning outcomes. Based on the results of research on the evaluation of the Islamic Religious Education learning program using the CIPP model obtained an average percentage of 81% with a very good category based on the results of the input evaluation of 78% with a good category, process evaluation of 85% with a very good category and product evaluation of 86% with a very good category. As a recommendation, this study suggests concrete solutions such as focused training for teachers, utilization of technology in learning, using active learning methods and providing additional learning to students so as to create effective and quality learning. The evaluation of the learning process also highlighted the need for guidance to teachers in making and operating learning media.